2012
DOI: 10.1124/jpet.112.194837
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Direct Thrombin Inhibition with Dabigatran on Plaque Formation and Endothelial Function in Apolipoprotein E-Deficient Mice

Abstract: The recently developed oral anticoagulant dabigatran (Dabi) etexilate directly inhibits thrombin after activation by plasma esterases to dabigatran. Thrombin is involved in the pathogenesis of atherosclerosis. We investigated the effects of direct thrombin inhibition on atherosclerosis and endothelial function in a hypercholesterolemic mouse model with accelerated atherosclerosis {[apolipoprotein E-deficient (ApoE(Ϫ/Ϫ)] mice}. ApoE(Ϫ/Ϫ) mice were treated with a cholesterol-rich diet for 12 weeks and either dab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 29 publications
5
73
0
7
Order By: Relevance
“…In the context of atherogenesis and atherosclerosis, TG is linked to early atherosclerosis, likely one of the drivers of this complex process 75. This model is strongly supported by experimental studies 22, 23, 24, 25…”
Section: Biochemical Mechanisms Linking Thrombin To Atherothrombosismentioning
confidence: 69%
“…In the context of atherogenesis and atherosclerosis, TG is linked to early atherosclerosis, likely one of the drivers of this complex process 75. This model is strongly supported by experimental studies 22, 23, 24, 25…”
Section: Biochemical Mechanisms Linking Thrombin To Atherothrombosismentioning
confidence: 69%
“…Moreover, hypercoagulability is linked to plaque phenotype [51], with effects that support either plaque stability or instability, depending on the plaque stage and the age of the animal, respectively [69,70]. These effects may well be clinically relevant, as three experimental studies have shown that the thrombin inhibitor dabigatran substantially attenuates atherosclerosis in apoE -/-mice [70][71][72]. Although these observations in mouse models are obviously not directly translatable to humans, even minute effects in humans may turn out to be relevant upon prolonged exposure to anticoagulants.…”
Section: Resultsmentioning
confidence: 99%
“…NOACs are very small molecules that will easily pass the endothelium and interact with coagulation proteases in the vessel wall. Indeed, a number of experimental studies have shown that administration of dabigatran inhibits atherogenesis in mice with an apoE null background, prone to develop atherosclerosis [47][48][49]. These studies also indicated several protective mechanisms resulting from thrombin inhibition, including endothelial cell protection, reduced inflammation by diminished neutrophil influx, and increased plaque stability.…”
Section: Nonhemostatic Functions Of Fiia and Fxa Inhibitorsmentioning
confidence: 99%